Sobre a estabilidade de ondas estacionárias para a equação de Schrödinger não linear - Thyago Souza Rosa Santos (2021)
The present work has a main characteristic the study of orbital stabilty and instability about standing waves for the nonlinear Schrödinger equation. More speciafically, we show the existence of standing waves through a variational approach. Then, we presente method developed to study the stability of standing waves, base mainly on compacteness argumentes and spectral properties of the linearized operator. Finally, we present results on the bound states instability for abstract dispersive systems, thus include a class of dispersive equations of insterest.